Gel-forming properties of red tilapia (Oreochromis niloticus) surimi as affected by selected additives - Bagher Seighalani, Fariba Zad (2012)
Surimi and surimi-based fish product are native to Japan; however, its consumption has spread to many parts of the world. Gel-forming ability of surimi is the main indicator for its quality, which is affected by factors such as the addition of food grade additives and fish species. Therefore, the objectives of this study were to identify the gel-forming properties of red tilapia surimi, to improve the physical, thermal, rheological and chemical properties of surimi gels by the addition of different concentrations of sodium pyrophosphate (SPP) (in combination with 2.5% CaCh), transglutaminase (TGase) and chitosan. The physico-chemical characteristics of the surimi gel were evaluated based on the kamaboko gel which were prepared by a 2-stage heating at 40°C for 20 min and 90°C for 30 min. Different levels of trans glutaminase ranging from 0.10 to O.SO%, chitosan ranging from O.SO to 1.S%, and SPP ranging from 0.0 to 0.04% (in combination with CaCh) were added to the surimi before the preparation of kamaboko gels. The kamaboko gel without any additives was used as the control. An increasing trend of Ca2+-ATPase activity was obtained in the surimi and kamaboko gel compared to the fish mince. The values for fish mince, surimi and kamaboko gel of red tilapia were 0.17 ± 0.04, 0.27 ± 0.01 and 0.20 ± O.OSumol Pi/mg protein/min, respectively. The hardness and chewiness were significantly (p<O.OS) different between the fish mince and kamaboko gels. Significant increase in maximum storage modulus (G') was observed in the kamaboko and surimi compared to the fish mince. The intensity of myosin heavy chain (MHC) band in the kamaboko gel was higher than the fish mince and surimi. No significant (p>O.OS) changes were observed in the intensity of actin band of fish mince, surimi and kamaboko. The differential scanning calorimetry (DSC) thermograms of fish mince showed three peaks at 41.0°C, S4.S0C and 72.0°C; however, only two peaks were obtained at 40.2°C and 74°C in surimi and 41.S0C and 72.S0C in kamaboko gel. A smaller enthalpy change (~H) of the myosin peak was obtained from the kamaboko gel as compared to the fish mince and surimi, but no significant (p>O.OS) difference was observed in the ~H of actin for the fish mince, surimi and kamaboko. The type and levels of the additives had significant effect (p<O.OS) on the breaking force and deformation of the samples. Samples containing 0.30% TGase showed the highest breaking force and deformation. The addition of TGase at > 0.30% and that of chitosan > 1.2S% resulted in the decrease in the breaking force and deformation of the kamaboko gels. Gels with 0.30% TGase, 1.25% chitosan and 0.05% SPP separately had lowest expressible content among treatments. Different levels of additives had significant effect on the gel whiteness. Gels with 0.50% TGase showed the highest value of whiteness. Additives used had significant effect on the myosin heavy chain band intensity, but no marked changes in the actin band intensity were observed. The MHC band almost disappeared with the addition of TGase at 0.30%. Significant increase in the G'max was observed in gels with additives compared to the control gel. Addition of additives had significant effect on the ~H, maximum transition temperature (Tm) of the myosin and ~H of actin (p<0.05) but slight differences between the Tm of actin was observed.